Type 1 diabetes mellitus and multiple sclerosis: common etiological features. - Handel, A; Handunnetthi, L; Ebers, G; Ramagopalan, S (2009)
Type 1 diabetes mellitus and multiple sclerosis have been largely seen as different, organ-specific diseases, which are managed by different medical specialties. Research studies on these diseases have for the most part followed independent tracks. In this Review, we highlight the latest epidemiological and genetic findings, which have identified many features common to both disorders. Experts consider it increasingly likely that the environment contributes substantially to this overlap. However, although genetic elements that are distinct to each disease probably determine the ultimate form of autoimmunity that is manifested, strikingly broad parallels are seen between the components of genetic risk of type 1 diabetes mellitus and multiple sclerosis. Similarities and differences between these two diseases draw attention to shared disease pathways but insights into each disorder are providing mutual illumination of their pathogenesis.